Catheter Associated Urinary Tract Candida Infections in Intensive Care Unit Patients - Sachin C Deorukhkar; Santosh Saini; Namita A Raytekar; M Dawna Sebastian (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2016)
Introduction: Health care associated infections (HCAIs) or nosocomial infections have a propensity to strike in the critical care areas. Surveillance of HCAIs, so as to defi ne the magnitude and nature of the problem, is the primary step towards reducing the risk for infection in vulnerable hospitalized patients. The present study was conducted in a rural tertiary care teaching hospital with an aim to determine the rate of catheter associated urinary tract Candida infections in medical intensive care unit patients. Methods: A prospective study was done on catheter associated urinary tract infection (CAUTI). The urine samples were collected and processed following standard microbiological protocols. Results: The overall rate of CAUTI was found to be 1.6 per 1000 catheter days. The rates of catheter associated bacteriuria and candiduria in our health care setup were noted as 1.2 and 0.4 respectively. Conclusion: The present surveillance study helped us to generate institutional data regarding CAUTI in ICU patients with a special reference to candiduria. In our institute, the incidence of candiduria was low.